Development of a theoretical framework for examining youth worker perspectives on their relationships with adolescents and emerging adults in the United States. (November 2021) - Forrester, Patrice
It is important to understand how youth workers perceive their work with clients to support them in facilitating positive outcomes (e.g., gainful employment, academic achievement) for those they serve. There is a paucity of peer-reviewed research that explores youth workers' perspectives on their social service practices in the United States despite their integral role in supporting positive adolescent and emerging adult development. This article discusses a theoretical framework founded on anthropology and social work paradigms. Researchers can use this theoretical framework to examine youth worker perspectives on building relationships with adolescents and emerging adults in the United States.